Evaluation of global horizontal irradiance estimates from ERA5 and COSMO-REA6 reanalyses using ground and satellite-based data. (April 2018) - Urraca, Ruben; Huld, Thomas; Gracia-Amillo, Ana; Martinez-de-Pison, Francisco Javier; Kaspar, Frank; Sanz-Garcia, Andres
Highlights: ERA5 and COSMO-REA6 reduce the quality gap between reanalysis and satellite data. ERA5 bias is similar to that of satellite data for inland regions with few clouds. COSMO-REA6 is comparable to ERA5 for North and Central Europe. The absolute error of reanalyses is large due to a deficient cloud prediction. COSMO-REA6 underestimates due to the overestimation of aerosols. Abstract: This study examines the progress made by two new reanalyses in the estimation of surface irradiance: ERA5, the new global reanalysis from the ECMWF, and COSMO-REA6, the regional reanalysis from the DWD for Europe. Daily global horizontal irradiance data were evaluated with 41 BSRN stations worldwide, 294 stations in Europe, and two satellite-derived products (NSRDB and SARAH). ERA5 achieves a moderate positive bias worldwide and in Europe of +4.05 W / m 2 and +4.54 W / m 2 respectively, which entails a reduction in the average bias ranging from 50% to 75% compared to ERA-Interim and MERRA-2. This makes ERA5 comparable with satellite-derived products in terms of the mean bias in most inland stations, but ERA5 results degrade in coastal areas and mountains. The bias of ERA5 varies with the cloudiness, overestimating under cloudy conditions and slightly underestimating under clear-skies, which suggests a poor prediction of cloud patterns and leads to larger absolute errors than that of satellite-based products. In Europe, the regional COSMO-REA6 underestimates in most stations (MBE = −5.29 W / m 2 ) showing the largest deviations under clear-sky conditions, which is most likely caused by the aerosol climatology used. Above 45°N the magnitude of the bias and absolute error of COSMO-REA6 are similar to ERA5 while it outperforms ERA5 in the coastal areas due to its high-resolution grid (6.2 km). We conclude that ERA5 and COSMO-REA6 have reduced the gap between reanalysis and satellite-based data, but further development is required in the prediction of clouds while the spatial grid of ERA5 (31 km) remains inadequate for places with high variability of surface irradiance (coasts and mountains). Satellite-based data should be still used when available, but having in mind their limitations, ERA5 is a valid alternative for situations in which satellite-based data are missing (polar regions and gaps in times series) while COSMO-REA6 complements ERA5 in Central and Northern Europe mitigating the limitations of ERA5 in coastal areas.